Unlocking amyotrophic lateral sclerosis: the role of adiponectin in inflammation and disease progression - Mei Tian; Mei Tian; Mei Tian; Cheng Xin; Cheng Xin; Cheng Xin; Jia Huo; Jia Huo; Jia Huo; Qi Liu; Qi Liu; Qi Liu; et al. (Frontiers in Neurology)
IntroductionIn amyotrophic lateral sclerosis (ALS), immune cells become activated, resulting in a persistent pro-inflammatory milieu and contributing to the development of ALS. Adiponectin produces anti-inflammatory effects via its adiponectin receptor 1 (AdipoR1) and adiponectin receptor 2 (AdipoR2). Currently, there has been limited research conducted on the correlation between adiponectin and inflammation in ALS.MethodsThis cross-sectional study recruited a cohort of 82 ALS patients and 25 controls. Adiponectin and inflammatory mediators in plasma were measured using enzyme-linked immunosorbent assay (ELISA). Furthermore, flow cytometry, immunocytochemistry, and ELISA were employed to examine the levels of AdipoR1, AdipoR2, and inflammatory markers in monocytes and macrophages obtained from ALS patients. The effects of Adiponectin receptor agonists (AdipoRon) on AdipoR expression, inflammatory responses, and macrophages polarization were investigated.ResultsPlasma adiponectin level in ALS patients was markedly lower than controls. This decrease was found to be positively associated with IL-1β, IL-2, IL-6, IL-8, and TNF-α, while negatively correlated with IL-4 and IL-10. Furthermore, there was a positive correlation between plasma adiponectin level and ALS Functional Rating Scale-Revised (ALSFRS-R), and a negative correlation with the disease progression rate (δFS). Mediation research demonstrated that IL-2, or TNF-α, or IL-10 acted as a mediator between adiponectin and δFS. AdipoR1 and AdipoR2 showed a notable increase in expression in peripheral blood monocytes and activated macrophages obtained from ALS patients, concomitant with elevated level of IL-1β. AdipoRon treatment resulted in a decrease in the expression of AdipoR1. Simultaneously, AdipoRon decreased the levels of IL-1β and MHC-II, while boosting the levels of IL-10 and CD206. This regulation enabled the transformation of macrophages from the M1 to the M2 phenotype, therefore aiding in the protection of neurons.ConclusionOur findings demonstrated a notable association between adiponectin level and inflammation in the peripheral regions of ALS patients. These results may offer new understanding into the control of inflammation and propose a possible treatment approach for ALS.